Study of the responses of two biomonitor plant species (Datura alba & Ricinus communis) to roadside air pollution. (November 2019) - Khalid, Noreen; Masood, Atifa; Noman, Ali; Aqeel, Muhammad; Qasim, Muhammad
Abstract: Various physiological and biochemical responses of two good biomonitor plant species i.e. Datura alba and Ricinus communis were studied along two roads in the Punjab, Pakistan. Chlorophyll a, b, total chlorophylls, carotenoids, total free amino acids, total soluble proteins, total antioxidant activity, stomatal conductance, photosynthetic rate, internal CO2 concentration, transpiration rate, and water use efficiency of D. alba and R. communis were examined at different sites along both roads. Photosynthetic rate of both plant species was found to be affected. Reduced transpiration rate and stomatal conductance were also noted. However, elevated internal CO2 concentration and water use efficiency were recorded. Total soluble proteins got reduced, but, we found a tremendous increase in total antioxidant activity and total free amino acids in both plant species. D. alba was found to be more affected by the adverse effects of roadside air borne pollutants. Although R. communis was also affected but it showed minimal variation in all parameters compared to the control. Hence, our results suggest that R. communis is more resistant to urban roadside air pollution compared to D. alba and would be a good choice as phytoremediator of traffic borne pollutants, whereas, D. alba could be a better biomonitoring plant. Highlights: Vehicle exhaust is the biggest sources of air pollution these days. Biological effects of vehicle pollution can be assessed by the use of biomonitoring plants. R. communis and D. alba are two effective biomonitoring plants. They responded differently to vehicle exhaust pollution at roadsides. R. communis could be a good phytoremediator, while, D. alba can be used as a bioindicator plant at roadsides.